Application of Heuristic Evaluation Method to Evaluate User Experience and User Interface of Personnel Management Information Systems to Improve Employee Performance - Fatkhuri; Dharmawan, Donny; Desty Febrian, Wenny; Karyadi, Sugeng; Sani, Indra (Jurnal Informasi dan Teknologi, 2024)
This research aims to determine the level of user satisfaction with using SIMPEG application and evaluate the user interface design to improve the user experience. The research was conducted using qualitative methods. Researchers decided to involve as many as 100 participants in this research. To collect data and information based on system requirements, researchers collect data using observation, interviews, questionnaires, and literature studies. In designing the evaluation at application, researchers used a user-centered design approach and the heuristic evaluation method. Based on the research results, it was found that in the UCD approach, it often experiences bugs and errors, whereas in application there is no mobile application available, which aims to make it easier for employees to access the application anywhere and anytime. It is currently only available on a web basis. The UCD approach shows that the application has uses and functions that meet employee expectations with an average percentage of 70%, falling into the attractive category. The end result of the UCD approach emphasizes the importance of clearly understanding users and providing better user experiences. Meanwhile, the HE approaches helps identify problems with the application and focuses attention on usability issues in the HE aspects. In an effort to improve the quality of the user interface (UI) and user experience (UX) in application, the evaluation that has been carried out shows that improvements need to be focused on the appearance and use of the application.